FASTING THERAPY AS SELF-CONTROL - Sholehati Rofi'ah Jamil (International Journal of Islamic and Complementary Medicine, 2021)
Fasting is familiar for Muslims around the world. One of the compulsory worship for Muslims is fasting during Ramadhan. Fasting is refraining from something that breaks fasting with a specific intention—fasting from dawn to sunset. Fasting not only suppresses appetite for food and drink but also restrains desire during the day. Fasting can also be said to be self-controlling from things that are detrimental or negative. We know that the current era of globalization has dramatically changed the pattern of people's lives. Good in terms of dress, talk, and food. Therefore this paper discusses fasting therapy as self-control. Various studies explained that fasting and getting the reward of fasting could also control emotions, avoid various diseases, and elevate human beings for the better. A person who does fasting will sincerely get a reward, the remission of sins, both sins in the past and sins that will come.